Model predictive direct suspension force control of a bearingless induction motor based on sliding mode observer. Issue 2 (30th November 2021) - Wu, Jiajie; Yang, Zebin; Sun, Xiaodong; Wang, Ding
Abstract : Purpose: The purpose of the control method proposed in this paper is to address the problem of the poor anti-interference of the suspension winding current in the traditional bearingless induction motor (BL-IM) direct suspension force control process. Design/methodology/approach: A model predictive direct suspension force control of a BL-IM based on sliding mode observer is proposed in this paper. The model predictive control (MPC) is introduced to the traditional direct suspension force control to improve the anti-interference of the suspension current. A sliding mode flux linkage observer is designed and applied to the MPC system, which reduces the error of the parameter observation and improves the robustness of the system. The strategy is designed and implemented in the MATLAB/Simulink and the two-level AC speed regulation platform. Findings: The simulation and experimental results show that the performance of the BL-IM under the control method proposed in this paper is better than that under the traditional direct suspension force control, and the suspension performance of the motor and the anti-interference of the control system are improved. Originality/value: This study helps to improve the suspension performance of the motor and the anti-interference of the control system.